Spiritualism in Ghãtu (Bon Voyage, 2019)
Ghãtu is fully based on spiritual practices. The ethnic group, Gurung observes this Ghãtu for good harvesting and faith healing. The performers believe that some of the diseases are healed after taking part in the dance performance. There are several benefits of observing the performance. When Ghãtu god is happy the villagers are protected from various kinds of bad luck. The villagers also believe that there will be good harvest after the performance. One most surprising thing is that the protagonist, Yempahawati self immolates for spiritual unification with her husband in the heaven. She believes that she will surely meet her husband in the spiritual world. She does not care of the throne, neither does she care her breast feeding two and half years old boy, Bala Krishna. She is no more interested in such material things. Therefore, this performance is full of spiritual practices.